Combining Host Genetics and Functional Analysis to Depict Inflammasome Contribution in Tuberculosis Susceptibility and Outcome in Endemic Areas - Souza De Lima, Dhêmerson; Bomfim, Caio C. B.; Leal, Vinícius N. C.; Reis, Edione C.; Soares, Jaíne L. S.; Fernandes, Fernanda P.; Amaral, Eduardo P.; Loures, Flavio V.; Ogusku, Mauricio M.; Lima, Maria R. D'Imperio; Sadahiro, Aya; Pontillo, Alessandra (Frontiers in Immunology, 2020)
The interplay between M.tuberculosis (Mtb) and humans is multifactorial. The susceptibility/resistance profile and the establishment of clinical tuberculosis (TB) still remains elusive. The gain-of-function variant rs10754558 in NLRP3 gene (found in 30% of world population) confers protection against the development of TB, indicating a prominent role of NLRP3 inflammasome against Mtb. Through genotype-guided assays and various Mtb strains (BCG, H37Rv, Beijing-1471, MP287/03), we demonstrated that Mtb strains activate inflammasome according to NLRP3/IL-1ß or NLRC4/IL18 preferential axis. NLRP3 and NLRC4 genetic variants contribute to TB presentation. For the first time we reported that loss-of-function variants in NLRC4 significantly contribute to the development of extra-pulmonary TB. The analysis of inflammasome activation in a cohort of TB patients and their “house contacts” (CNT) revealed that plasma IL-1ß/IFN-α ratio lets us distinguish patients from Mtb-exposed-but-healthy individuals from endemic region. Moreover NLRP3 inflammasome resulted “exhausted” in TB patients compared to CNT, indicating a more efficient activation of inflammasome in resistant individuals. These findings suggest that inflammasome genetics as well as virulence-dependent entity of inflammasome activation contribute to susceptible/resistant profile of Mtb-exposed individuals.